Legal environment affecting the foodgrain trade - Rahman, Shamsur (International Food Policy Research Institute, 2000)
The Government of India issued a wartime Proclamation of Emergency on September 3, 1939, empowering the federal government to enact legislation on any subject it deemed proper—even areas normally within the sole purview of the provincial legislatures, such as the production, trade, and distribution of foodstuffs. This legislation encompassed all of British India, including the present-day countries of Bangladesh, India, and Pakistan. During World War II the government continued to regulate the production, treatment, storage, movement, transport, distribution, disposal, acquisition, use, and consumption of many essential commodities, including foodgrains. Provincial governments also instituted measures establishing controls on foodgrain supply, including direct government procurement and distribution.